HUMAN RESOURCE MANAGEMENT EFFECTIVENESS ON MULTICULTURAL ORGANIZATION BASED ON SWOT PERSPECTIVE - Nurmeidiana, Mourizqa; Khalid , Zulvia (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Globalization has led to a rise in multicultural work environments, requiring organizations to understand cultural differences and adapt to internal dynamics. This study uses PM Fresh, an Australian food product company, to explore how Human Resource Management (HRM) strategies can address cultural differences and enhance organizational performance. Strategic SDM practices, such as language training, cultural competency development, and flexible work arrangements, are crucial for achieving this goal.